Kemampuan Siswa Menghafal Al-Qur’an melalui Metode Talaqqi di Madrasah Tsanawiyah Abbasiyah Teluk Pinang Kecamatan Gaung Anak Serka - Siagian, Seri Yanti; Riko, Riko (Penerbit Goodwood, 2024)
Purpose: This article aims to determine students' ability to memorize the Al-Qur'an using the talaqqi method at Madrasah Tsanawiyah Abbasiyah Teluk Pinang, Gaung Anak Serka District. Research methodology: The informants in this research were 1 teacher of tahfidz Al-Qur'an and 91 students of Madrasah Tsanawiyah Abbasiyah Teluk Pinang, Gaung Anak Serka District who took tahfizh Qur'an subjects. The instruments used in this study were tests and interviews. Tests and interviews were conducted to assess the students' ability to memorize the Koran using the Talaqqi method. The data analysis used by the researchers was conducted by Milles and Hubermen, where the steps used were data reduction, data display, and data verification. Results: The results of the research found that students' ability to memorize the Al-Qur'an through the talaqqi method at Madrasah Tsanawiyah Abbasiyah Teluk Pinang, Gaung Anak Serka District was very good, this can be seen in the total number of scores obtained by students in the Al-Qur'an memorizing ability test was 7,981/ 91 = 87.70% and is categorized as very good, because the figure 87.70% lies in the interval 81% - 100%. Based on the research results, we conclude that the ability of students to memorize the Qur'an through the talaqqi method in Madrasah Tsanawiyah Abbasiyah Teluk Pinang, Gaung Anak Serka District is very good because 87.70% lies in the interval 81%–100%, as seen from the test results. carried out by teachers and students in tahfizh Qur'an learning activities, students can read and memorize the Qur'an fluently, their memorization is in accordance with their tajwid knowledge, and their memorization is also in accordance with makharijul letters and fashah. Limitation: Some children whose abilities are still weak because their reading of the Qur'an is not yet fluent. Contribution: Madrasah Tsanawiyah in the Indragiri hilr district has a Tahfizh Qur'an program.